1973
DOI: 10.1055/s-0028-1091731
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Sural Nerve in Neuronal Ceroid-Lipofuscinoses: Report of Two Cases

Abstract: A. Involvement of sural nerve in neuronal ceroid-lipofuscinoses. Neuropadiatrie Band 3:98-110(1973). Findings in sural nerve biopsies in two patients with neuronal ceroid lipofuscinosis are described. In Schwann-cells and in smooth muscle cells of vessels curvilinear-and fingerprintmaterial were demonstrated. The report discusses the significance of these findings. The clinical findings were in agreement with a diagnosis of late infantile and juvenile type respectively. Ultrastructurally there were signs of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…The criteria we used for assigning children to each of these classical types are described in Table 1. Particular attention was paid to atypical cases encountered in our material and in that of others [Van Bogaert, 1961;Joosten et al, 1973;Da1 Canto et al, 1974;Lou and Kristensen, 1973;Carpenter et al, 1973;Lyon, 1975;Jervis and Donahue, 1975;Goebel et al, 1976;Lake and Cavanagh, 1978;Barlow and Williams, 1979;Dom et al, 1979;Badurska et al, 1981;Libert et al, 1982;Nau et al, 1984;Wisniewski et al, 1985a,b, 19871. No specific biochemical or molecular diagnostic marker for NCL has been identified. Analyses of the lipopigment, and of dolichols which have an important function TABLE 1.…”
Section: Introductionmentioning
confidence: 81%
“…The criteria we used for assigning children to each of these classical types are described in Table 1. Particular attention was paid to atypical cases encountered in our material and in that of others [Van Bogaert, 1961;Joosten et al, 1973;Da1 Canto et al, 1974;Lou and Kristensen, 1973;Carpenter et al, 1973;Lyon, 1975;Jervis and Donahue, 1975;Goebel et al, 1976;Lake and Cavanagh, 1978;Barlow and Williams, 1979;Dom et al, 1979;Badurska et al, 1981;Libert et al, 1982;Nau et al, 1984;Wisniewski et al, 1985a,b, 19871. No specific biochemical or molecular diagnostic marker for NCL has been identified. Analyses of the lipopigment, and of dolichols which have an important function TABLE 1.…”
Section: Introductionmentioning
confidence: 81%
“…Examination of biopsy material from tissues more easily accessible than the central nervous system has therefore been used for diagnostic purposes in these disorders. Rectal or appendical biopsies have been most frequently performed for this purpose (Fawcett et al, 1966;Haelst and Gabreels, 1972;Rapola and Haltia, 1973), but peripheral nerve biopsy has also been proposed (Joosten et al, 1973) as well as examination of blood lymphocytes (Witzleben et al, 1971).…”
mentioning
confidence: 99%
“…Kristensson et al (1967) found pathoanatomical changes in necropsy material, and Joosten et al (1973) found ultrastructural changes in biopsies of the sural nerve in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological and biochemical investigations have, however, demonstrated signs of more generalized pathological features (Carpenter et al, 1972;Joosten et al, 1973;Rapola and 1 This study was part of a multidisciplinary investigation by the Scandinavian Spielmeyer.Vogt Group Centrallaboratoriet, Kolonien Filadelfia, 5293 Dianalund,Denmark. (Accepted 20 August 1974.) Haltia, 1973).…”
mentioning
confidence: 99%